2001
DOI: 10.1007/s005350170097
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological study of hepatitis E virus infection in Japan using a newly developed antibody assay

Abstract: Our results suggest the possibility that HEV infection is circulating in Japan at a low level. HEV infection was associated with male sex, but not with HAV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 25 publications
5
13
0
Order By: Relevance
“…In the present study conducted in Japan, where HEV infection is not considered endemic, 11 (12.6%) of 87 patients who had previously been diagnosed with sporadic acute hepatitis of non-ABC etiology were found to be infected with HEV. The prevalence of HEV RNA differed by age, sex, and geographic region, being consistent with the reported age-, sex-, and region-dependent prevalence of anti-HEV IgG in healthy individuals in Japan (21,41). Interestingly, in our present study, the prevalence of HEV-associated hepatitis among sporadic acute hepatitis cases of non-ABC etiology was significantly associated with male sex, older age (Ն40 years), and living in the northern part of Japan (Hokkaido and Iwate) (P Ͻ 0.01, P Ͻ 0.005, and P Ͻ 0.05, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…In the present study conducted in Japan, where HEV infection is not considered endemic, 11 (12.6%) of 87 patients who had previously been diagnosed with sporadic acute hepatitis of non-ABC etiology were found to be infected with HEV. The prevalence of HEV RNA differed by age, sex, and geographic region, being consistent with the reported age-, sex-, and region-dependent prevalence of anti-HEV IgG in healthy individuals in Japan (21,41). Interestingly, in our present study, the prevalence of HEV-associated hepatitis among sporadic acute hepatitis cases of non-ABC etiology was significantly associated with male sex, older age (Ն40 years), and living in the northern part of Japan (Hokkaido and Iwate) (P Ͻ 0.01, P Ͻ 0.005, and P Ͻ 0.05, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, there was no appreciable difference in the prevalence of anti-HEV IgG at the start of hemodialysis between the patients who did or did not have a past history of blood transfusion (8.3% [9/109] vs. 10.7% [33/307], P ¼ 0.5776), suggesting that the HEV infection in our hemodialysis patients that was acquired before the initiation of hemodialysis, had not been acquired by blood transfusion in the majority of cases. Of note, the prevalence of anti-HEV IgG at the start of hemodialysis tended to be higher among males than among females (11.7 vs. 7.0%), similar to the reported higher prevalence of anti-HEV IgG among males in the general population and the higher prevalence of HEVassociated hepatitis among male patients who had no history of blood transfusion within one or more years before the onset of disease [Tanaka et al, 2001;Mizuo et al, 2002]. Therefore, we would consider the possibility that our patients who were positive for anti-HEV IgG at the start of hemodialysis had acquired HEV infection in the community.…”
Section: Discussionsupporting
confidence: 83%
“…Although the results cannot simply be generalized for the whole country, previous studies on the age-specific prevalence of HAV and/or HEV infections revealed similar changing trends in other urban and rural areas including Metropolitan Tokyo, a small district of South Kiso town located between Aichi and Tokyo, and Okinawa in Japan [Furusyo et al, 1998;Tanaka et al, 2001Tanaka et al, , 2005Malaty et al, 2003].…”
Section: Discussionsupporting
confidence: 62%